Evaluation of Compacted Forage Feed on Kupang Cattle Feeding Behavior - Fensa Eka Widjaya; Despal Despal; Yuli Retnani; Rudy Priyanto; Luki Abdullah (Buletin Peternakan, 2022)
Forage  compact  feed  has  the  ability  to  cut  the  adaptation  period  of  grazing cattle when transported, because they are used to consume forage. The effect of the form and  type  of  forage  formulation  on  the  feeding  behavior  of  cattle  needs  to  be  studied further to determine the preferences of cattle for this compact feed. This study used 36 cattle  with  3  replications  in  each  treatment.  The  2  factor  groups  withfactorial  design consisting  formulation  and  form  of  feed  was  applied  in  this  study.  The  forms  of  feed used in this study were wafers, pellets, dried pellets, and cubes. The formulations used in  this  study  were  formulation  1  (10%  molasses,  30%  indigofera  leaves,  50%  straw, 10% elephant grass); formulation 2 (10% molasses, 30% indigofera leaves, 60% straw); formulation  3  (10%  molasses,  20%  indigofera  leaves,  65%  straw,  5% hemp).  The parameters observed in this study were eating behavior of cattle which consisted of the frequency and duration of eating, drinking, rumination, and resting. The results showed that there wasan interaction on eating frequency and cattle duration. Formulation 3 on wafer  treatment  had  the  highest  feeding  frequency  (P<0.05).  Formulation  1  on  wafer treatment   had   the   highest   duration   of   rumination   (P<0.05).   In   the   conclusion, Formulation 1 and 3 with wafer shape showed the best behavior for eating.